Dispersal in Adult Arctic Ground Squirrels: Why Do Males Do What They Do? - Gillis, Elizabeth (ARCTIC, 2002)
. The primary goal of my research on ground squirrels is to determine why adult males disperse. I use this system to understand the ecology of mating behaviour and the evolutionary implications of different mating strategies. Two hypotheses I am investigating are (1) that adult males disperse to avoid mating with their daughters, who breed very close to where they were born, and (2) that adult males disperse to increase their access to females for mating. I also quantify survival and reproductive costs and benefits associated with dispersal for adult males in order to identify potential explanations for the different mating strategies used by individuals within a population. To address these objectives, I study a population of arctic ground squirrels in the ruby ranges, located along the eastern shore of Kluane Lake, Yukon Territory. . I live-trap, ear-tag, and radio-collar adult male ground squirrels and follow them throughout the summers to determine dispersal distances and rates and adult male survival. To measure male reproductive success, I monitor the female population for signs of pregnancy and, after locating the pregnant females' natal nests, monitor them for the presence of juveniles. As the juveniles emerge, I trap them to determine litter sizes and take tissue samples. I am now analyzing the DNA of these tissue samples to determine which males sired which litters. . My data analysis is not yet complete, but preliminary results challenge many of the assumptions previously held about dispersal of adult arctic ground squirrels and male mating strategies in general. . The high survival rate among dispersers contradicts the common assumption that dispersing animals are at high risk of death. Interesting results are also emerging from the comparison of population dynamics of ground squirrels at the alpine and lower-elevation sites. The majority of mortality in the boreal forest population occurs because of predation during the active season, but overwinter mortality appears to contribute most to yearly ...